Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Form the indicated operations for the given functions. For these problems, treat each function independently from each other and from previous examples.

\begin{tabular}{|l|l|l|}
\hline System & Operation & Solution \\
\hline
[tex]$\left\{\begin{array}{l}f(x)=x^2+4 \\ g(x)=x-1\end{array}\right.$[/tex] & Find [tex]$(g+f)(x)$[/tex] & \\
\hline
[tex]$\left\{\begin{array}{l}g(x)=4x-1 \\ f(x)=x-2\end{array}\right.$[/tex] & Find [tex]$g(x)-f(x)$[/tex] & \\
\hline
[tex]$\left\{\begin{array}{l}g(x)=3x+1 \\ h(x)=2x-2\end{array}\right.$[/tex] & Find [tex]$(g-h)(x)$[/tex] & \\
\hline
[tex]$\left\{\begin{array}{l}g(x)=x^2-2x-1 \\ h(x)=2x-2\end{array}\right.$[/tex] & Find [tex]$g(x)+h(x)$[/tex] & \\
\hline
\end{tabular}


Sagot :

Let's solve the following problems step-by-step.

### Problem 1:
We are given the functions [tex]\( f(x) = x^2 + 4 \)[/tex] and [tex]\( g(x) = x - 1 \)[/tex]. We need to find [tex]\( (g+f)(x) \)[/tex].

To find [tex]\( (g+f)(x) \)[/tex], we need to add [tex]\( g(x) \)[/tex] and [tex]\( f(x) \)[/tex]:
[tex]\[ (g+f)(x) = g(x) + f(x) \][/tex]
Substitute the given functions:
[tex]\[ g(x) = x - 1 \][/tex]
[tex]\[ f(x) = x^2 + 4 \][/tex]
Thus,
[tex]\[ (g+f)(x) = (x - 1) + (x^2 + 4) \][/tex]
[tex]\[ (g+f)(x) = x^2 + x + 3 \][/tex]
For [tex]\( x = 2 \)[/tex]:
[tex]\[ (g+f)(2) = 2^2 + 2 + 3 \][/tex]
[tex]\[ (g+f)(2) = 4 + 2 + 3 \][/tex]
[tex]\[ (g+f)(2) = 9 \][/tex]

So, the value is [tex]\( 9 \)[/tex].

### Problem 2:
We are given the functions [tex]\( g(x) = 4x - 1 \)[/tex] and [tex]\( f(x) = x - 2 \)[/tex]. We need to find [tex]\( g(x) - f(x) \)[/tex].

To find [tex]\( g(x) - f(x) \)[/tex], we simply subtract [tex]\( f(x) \)[/tex] from [tex]\( g(x) \)[/tex]:
[tex]\[ (g-f)(x) = g(x) - f(x) \][/tex]
Substitute the given functions:
[tex]\[ g(x) = 4x - 1 \][/tex]
[tex]\[ f(x) = x - 2 \][/tex]
Thus,
[tex]\[ (g-f)(x) = (4x - 1) - (x - 2) \][/tex]
[tex]\[ (g-f)(x) = 4x - 1 - x + 2 \][/tex]
[tex]\[ (g-f)(x) = 3x + 1 \][/tex]
For [tex]\( x = 2 \)[/tex]:
[tex]\[ (g-f)(2) = 3 \cdot 2 + 1 \][/tex]
[tex]\[ (g-f)(2) = 6 + 1 \][/tex]
[tex]\[ (g-f)(2) = 7 \][/tex]

So, the value is [tex]\( 7 \)[/tex].

### Problem 3:
We are given the functions [tex]\( g(x) = 3x + 1 \)[/tex] and [tex]\( h(x) = 2x - 2 \)[/tex]. We need to find [tex]\( (g-h)(x) \)[/tex].

To find [tex]\( (g-h)(x) \)[/tex], we need to subtract [tex]\( h(x) \)[/tex] from [tex]\( g(x) \)[/tex]:
[tex]\[ (g-h)(x) = g(x) - h(x) \][/tex]
Substitute the given functions:
[tex]\[ g(x) = 3x + 1 \][/tex]
[tex]\[ h(x) = 2x - 2 \][/tex]
Thus,
[tex]\[ (g-h)(x) = (3x + 1) - (2x - 2) \][/tex]
[tex]\[ (g-h)(x) = 3x + 1 - 2x + 2 \][/tex]
[tex]\[ (g-h)(x) = x + 3 \][/tex]
For [tex]\( x = 2 \)[/tex]:
[tex]\[ (g-h)(2) = 2 + 3 \][/tex]
[tex]\[ (g-h)(2) = 5 \][/tex]

So, the value is [tex]\( 5 \)[/tex].

### Problem 4:
We are given the functions [tex]\( g(x) = x^2 - 2x - 1 \)[/tex] and [tex]\( h(x) = 2x - 2 \)[/tex]. We need to find [tex]\( g(x) + h(x) \)[/tex].

To find [tex]\( g(x) + h(x) \)[/tex], we need to add [tex]\( g(x) \)[/tex] and [tex]\( h(x) \)[/tex]:
[tex]\[ (g+h)(x) = g(x) + h(x) \][/tex]
Substitute the given functions:
[tex]\[ g(x) = x^2 - 2x - 1 \][/tex]
[tex]\[ h(x) = 2x - 2 \][/tex]
Thus,
[tex]\[ (g+h)(x) = (x^2 - 2x - 1) + (2x - 2) \][/tex]
[tex]\[ (g+h)(x) = x^2 - 2x - 1 + 2x - 2 \][/tex]
[tex]\[ (g+h)(x) = x^2 - 3 \][/tex]
For [tex]\( x = 2 \)[/tex]:
[tex]\[ (g+h)(2) = 2^2 - 3 \][/tex]
[tex]\[ (g+h)(2) = 4 - 3 \][/tex]
[tex]\[ (g+h)(2) = 1 \][/tex]

So, the value is [tex]\( 1 \)[/tex].